Parents' Participation in Care during Neonatal Intensive Care Unit Stay in COVID-19 Era: An Observational Study - Emanuele Buccione; Davide Scarponcini Fornaro; Damiana Pieragostino; Luca Natale; Adelaide D'Errico; Valentina Chiavaroli; Laura Rasero; Stefano Bambi; Carlo Della Pelle; Susanna Di Valerio (MDPI AG, 2024)
Background: Parents play a crucial role in the care of infants during their stay in the neonatal intensive care unit (NICU). Recent studies have reported a decrease in parental participation due to the coronavirus disease (COVID-19) pandemic, which has led to restricted access policies in hospitals. The aim of this study was to describe the barriers to good parental participation during their stay in the neonatal intensive care unit in the COVID-19 era. Methods: This was a quantitative, observational study. Results: A total of 270 parents participated in this study. Mothers' participation in care was higher than that of fathers (p = 0.017). Parents who lived at the birth of their first child reported a better level of participation in care compared to those who lived at the birth of their second-born (p = 0.005). Parents of extremely preterm neonates reported a lower interaction with their infants than parents of term newborns (p < 0.001). Conclusions: Some disadvantaged categories reported lower scores for cultural and linguistic minorities, parents of multiple children, and fathers. The COVID-19 pandemic has made several family-centred care activities impossible, with a higher impact on those who benefited most of these facilities. This study was prospectively approved by the IRB-CRRM of the University "G. d'Annunzio" Chieti-Pescara on 23 January 2024 (approval number CRRM: 2023_12_07_01).